The Statesman's Yearbook 2009
1608 p.
Keywords: This edition is fully updated and contains more information and analysis than ever before. A foldout colour section provides a political world map and flags for all 193 countries. Each copy comes with online access to the full text at no extra cost. Unlimited-user upgrades are also available for libraries who wish to network the data.